Replacing Mineral with Organic Fertilisers in Maize Basal Fertilisation: Impacts on GHG Emissions and Yield - Catarina Esteves; Arejacy Antonio Silva; Mariana Mota; João Coutinho; Irene Fraga; David Fangueiro (Agronomy)
Portuguese farmers seek evidence that organic fertilisers, particularly manure-based ones, can be safely used as partial replacements for mineral fertilisers (MFs), taking advantage of their nutrient and organic matter (OM) content. This study aimed to clarify the effects of applying organic fertilisers, especially under no-till practices in maize production. The experiment involved replacing basal mineral nitrogen (N) fertilisation with composted animal manure (CM) and pig slurry (PS) across three contrasting fields with varying soil characteristics, tillage techniques, and OM supplementation. Results indicated that site 1, which had the lowest clay and OM content, benefited the most from organic fertilisers, particularly in enhanced nutrient absorption in both maize leaves and grain. In this site, partial nutrient balance of N was significantly higher in the PS treatment (0.56 kg grain N exported kg N applied−1) compared with the treatment with only MF (0.44). The impacts on greenhouse gas (GHG) emissions depended on site characteristics. CM led to higher emissions at site 2 (CH4) and site 3 (N2O), while PS did not increase GHG emissions at any site. Under no-till practices at site 3, CM resulted in higher global warming potential (154 kg CO2-eq ha−1) compared with the PS (128 kg CO2-eq ha−1) and MF (109 kg CO2-eq ha−1) treatments. Overall, this study suggests that organic fertilisers, particularly PS, can be a viable strategy for improving soil health and maintaining sustainable maize production in Portuguese agriculture. However, their effectiveness depends on factors such as soil texture, OM content, and tillage practices. In soils with lower OM content or under no-till practices, pig slurry emerges as a suitable alternative, replacing 30% of total mineral N fertilisation without compromising productivity or increasing GHG emissions.